«Ethical or cultural state» - Guzzone, Giuliano (International Gramsci Journal, 2025)
The article begins with the concept of the “Ethical or Cultural State”, which Gramsci inherits from Benedetto Croce but redefines in the Prison Notebooks with a non-Crocean meaning. He uses this concept to establish a relationship of unity and distinction between the educative function of the State (in the strict sense) and the multitude of «so-called private initiatives and activities that constitute the apparatus of the ruling classes’ political and cultural hegemony». This concept belongs to a broader semantic field, encompassing government by consent, the Ethical State sans phrase, and the State «in an organic and larger sense» (or integral State). The author demonstrates how Gramsci gradually moved beyond viewing civil society as merely an “intermediate level” tasked with exercising hegemony. Instead, he came to recognize hegemonic dynamics (and apparatuses) within the State itself (strictly defined) as well as in the “structure.” Thus, the “Ethical or Cultural State” represents a transitional stage in Gramsci’s intellectual trajectory – one that ultimately led him to acknowledge the ubiquity of hegemony and to reconceptualize the link between the integral State and the relations of production.